1983
DOI: 10.1530/jrf.0.0680401
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic control of the cyclic AMP-dependent protein kinase isoenzymes of the rat epididymis

Abstract: Summary. The specific activity of the type I and type II isoenzyme forms of the cAMP-dependent protein kinase (EC 2.7.1.37) in the caput epididymidis of the intact rat was less than that of the caudal region while the isoenzyme ratio (type II :type I) of the former was greater than that of the latter, with type II being the predominant form in both regions. By 7 days after castration, the specific activities in both regions had decreased to the same level. The isoenzyme ratio of the caudal region increased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…[ -32 ] would be used by protein kinases to form radioactive phosphorylated proteins. After the incubation, the tissue slices were separated from the medium, washed and the cytosolic fraction was prepared as described previously (Mongkolsirikieat & Chulavatnatol, 1983). Using 2-dimensional gel electrophoresis and autoradiography, the cytosolic fraction yielded a very complex pattern consisting of numerous radioactive proteins while the medium showed a simple pattern of fewer radioactive proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ -32 ] would be used by protein kinases to form radioactive phosphorylated proteins. After the incubation, the tissue slices were separated from the medium, washed and the cytosolic fraction was prepared as described previously (Mongkolsirikieat & Chulavatnatol, 1983). Using 2-dimensional gel electrophoresis and autoradiography, the cytosolic fraction yielded a very complex pattern consisting of numerous radioactive proteins while the medium showed a simple pattern of fewer radioactive proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Androgen withdrawal is known to prevent the synthesis of epididymal secretory proteins (Brooks, 1981b) and to decrease the activity and to change the isoenzymes of protein kinase (Mongkolsirikieat & Chulavatnatol, 1983). Both processes may contribute to the observed decrease in the phosphorylated secretory proteins from the androgen-deficient rats.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that many genes are expressed in the epididymis and are regulated by testicular endocrine and/or lumicrine signaling [ 6 , 13 , 16 , 24 , 31 , 34 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ,…”
Section: Discussionmentioning
confidence: 99%